2015
DOI: 10.3109/14992027.2014.997314
|View full text |Cite
|
Sign up to set email alerts
|

Prosody perception and musical pitch discrimination in adults using cochlear implants

Abstract: Cochlear implants (CIs) provide coarse representations of pitch, which are adequate for speech but not for music. Despite increasing interest in music processing by CI users, the available information is fragmentary. The present experiment attempted to fill this void by conducting a comprehensive assessment of music processing in adult CI users. CI users (n =6) and normally hearing (NH) controls (n = 12) were tested on several tasks involving melody and rhythm perception, recognition of familiar music, and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 101 publications
1
16
1
Order By: Relevance
“…Our review discusses how voice emotion processing, perception, and production may be hindered in CI users, and that the wide variability in CI performance is secondary to a number of factors including poor pitch representation and limited spectro436 temporal fine structure information. As a result, CI users may be forced to rely on cues other than frequency - such as intensity, tempo, and duration - to determine the intended emotion of a speaker (Kalathottukaren, et al, 2015). Other studies have shown that CI users are not particularly effective at using alternative strategies, and continue to rely most heavily on pitch information despite its poor quality for prosodic information (Meister et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our review discusses how voice emotion processing, perception, and production may be hindered in CI users, and that the wide variability in CI performance is secondary to a number of factors including poor pitch representation and limited spectro436 temporal fine structure information. As a result, CI users may be forced to rely on cues other than frequency - such as intensity, tempo, and duration - to determine the intended emotion of a speaker (Kalathottukaren, et al, 2015). Other studies have shown that CI users are not particularly effective at using alternative strategies, and continue to rely most heavily on pitch information despite its poor quality for prosodic information (Meister et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Adult and pediatric CI users consistently demonstrate significant deficits in target emotion recognition ((Luo, et al, 2007; Pereira, 2000; Kalathottukaren, et al, 2015; Hopyan-Misakyan, et al, 2009; Chatterjee, et al, 2015; Nakata, et al, 2012; Volkova, et al, 2012; Gilbers, et al, 2015) and other prosodic-dependent components of communication (e.g. question-statement discrimination, lexical tone languages, stress patterns in speech).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations